Population Density and Habitat Characteristics of Nipa Fruticans in Degraded Mangrove Ecosystem (Case Study in Mahakam Delta, East Kalimantan) - Nurul Silva Lestari; R. Fatmi Noor’an (Journal of Wetlands Environmental Management, 2019)
Mahakam Delta is one of the largest mangrove ecosystem areas in East Kalimantan, which is dominated by nipa (Nypa fruticans). This paper investigates the population density of nipa and measures habitat characteristics in the area, which represents the condition of mangrove ecosystem that has received heavy pressures as a result of the increase in human activities.A total of 30 plots, size of 100m2 each plot, were sampled from six locations in the study site. In each plot, the number of individual, stalk, leaves, fruit and flower of nipa was recorded. Nipa zone adjacent to active ponds area had the density of 106 individual/ha with 913 stalks ha-1. The leaf density was 336 leaves ha-1, fruit density was 12 fruits ha-1 and flower density was 12 flowers/ha. Furthermore, nipa density in locations faraway from active ponds area was 74 individual/ha with 861 stalks/ha. While the leaf density was 239 leaves/ha, fruit density in this area was 2 fruits/ha and flower density was 9 flowers/ha. Result also showed that nipa habitat in study site is characterized by high turbidity and low salinity. Among other parameters, tidal level has strongest correlation to nipa population density. This study can also be considered as a preliminary assessment to develop mangrove ecosystem rehabilitation action plans in Mahakam Delta and to consider the potential use of nipa as an alternative source of livelihood for local communities living in the vicinity of the Mahakam Delta area.